A comparison of lower limb kinematics between superior and intermediate players in table tennis forehand loop - Zhang, Y.; Awrejcewicz, J.; Goethel, M.; Levadnyi, I.; Gu, Y. (ISBS Proceedings Archive (Michigan), 2017)
Understanding of biomechanics is important in sports performance enhancement since each skill has a fundamental mechanical structure. The purpose of this study was to investigate the effect of performance level on lower limb kinematics in table tennis forehand loop. 13 male superior players (SPs) and 13 intermediate players (IPs) participated in this test. A VICON motion analysis system was used to capture joint motions of lower limbs. Participants were asked to execute single forehand loop against topspin ball with full effort. Compared with IPs, SPs showed significantly larger hip flexion and knee external rotation at the event of backward-end, and larger hip internal rotation and extension at forward-end. SPs also showed significantly larger ankle and hip angular changing rate during forward swing.